An evaluation of a targeted group intervention delivered to year 8 pupils and broadly based on cognitive-behavioural approaches - Harding, Helen (2011)
This thesis describes the evaluation of a targeted group intervention that is broadly based on cognitive-behavioural approaches. The intervention incorporates aspects of social skills training and anger management training, and utilises the concepts of cognitive behavioural therapy. The intervention aims to promote emotional literacy and behavioural change and to impact upon school exclusions in secondary school pupils.